PENGUJIAN SELEKTIVITAS UJI KOLORIMETRI ( FAST BLUE B SALT) UNTUK IDENTIFIKASI METAMFETAMINA (MA) DAN METILENDIOKSIMETAMFETAMINA (MDMA) DALAM URINE DENGAN TLC, HPTLC DAN GCMS - supiyani; Ungkap Siahaan; Debora M. Hutagaol (Journal of Forensic Expert, 2022)
ABSTRACT This study examined the use of Fast Blue B Salt (FBBS) spray as a semi-confirmed colorimetric test in the urine examination of suspected Methamphetamine (MA) and Methylenedioxymethamphetamine (MDMA) narcotic suspects. The application of spray of Fast Blue B Salt with a concentration of 1000 ppm on urine extract which was spotted on an HPTLC silica gel 60 F254 plate was carried out at room temperature with eluent of Ethyl acetate: Methanol: Ammonia (8.5: 1: 0.5) with solvent of Chloroform: Isopropanol (1: 1) by using CRM MA and CRM MDMA comparison. The presence of MA and MDMA in the suspect's urine was identified by the appearance of a color on the TLC (Thin Layer Chromatography) plate, namely a yellowish orange color for positive MA with an Rf of 0.63 { on trak1 (urine 9416) and trak3 (urine 9577)} and a dark yellowish violet color for MDMA positive with Rf 0.67 { on track 2 (urine 9768A1) and track 4 (urine 9768B)} where the color and Rf of the compound are the same as the comparison color for track 5 (CRM MA) and track 6 (CRM MDMA). The selectivity of the new FBBS colorimetric test method for the color of MA and MDMA compounds on TLC plates was confirmed using HPTLC (High Performance Thin Layer Chromatography) and GCMS (Gas Chromatography Mass Spectroscopy). HPTLC and GCMS confirmation results on TLC plates that were previously Ma positive (urine 9416 and urine 9577) were confirmed to be positive for MA at 215 nm and 260 nm and Rt 3.6 MS m/z (149, 134, 91,58), as well as previously positive for MDMA (urine 9768A1 and urine 9768B) confirmed to be positive for MDMA at λ 215 nm, 240 nm and 280 nm and Rt 6.3 MS m/z (193, 178, 135, 89, 58). The occurrence of specific colors of MA compounds with yellowish orange color and dark violet-yellow MDMA by a new colorimetric test method (Fast Blue B Salt spray) can be tested for selectivity by TLC, HPTLC and GCMS. ABSTRAK Penelitian ini tentang penggunaan spray Fast Blue B Salt (FBBS) sebagai uji kolorimetri semi konfirmasi dalam pemeriksaan urine tersangka pengguna narkotika jenis Metamfetamina (MA) dan Metilendioksimetamfetamina (MDMA). Pengaplikasian spray Fast Blue B Salt konsentrasi 1000 ppm pada ekstrak urine yang ditotolkan pada plat HPTLC silica gel 60 F254 dilakukan pada suhu kamar dengan eluen Etil asetat : Metanol : Amoniak (8,5: 1 : 0,5) dengan pelarut Kloroform: Isopropanol (1 : 1) dengan menggunakan pembanding CRM MAdan CRM MDMA. Adanya MA dan MDMA didalam urine tersangka diidentifikasi dengan munculnya warna pada plat TLC (Thin Layer Chromatography) yaitu warna orange kekuningan untuk positif MA dengan Rf 0,63 { pada trak1 (urine 9416) dan trak3 (urine 9577)} dan warna violet tua kekuningan untuk positif MDMA dengan Rf 0,67 { pada trak 2 (urine 9768A1) dan trak 4 ( urine 9768B)} dimana warna dan Rf senyawa tersebut sama dengan warna pembanding trak 5 (CRM MA) dan trak 6 (CRM MDMA). Keselektivan metode baru uji kolorimetri FBBS terhadap warna senyawa MA dan MDMA pada plat TLC diuji konfirmasi dengan menggunakan HPTLC (High Performance Thin Layer Chromatography) dan GCMS (Gas Chromatography Mass Specrtroscopy). Hasil konfirmasi HPTLC dan GCMS terhadap plat TLC yang sebelumnya positif Ma (urine 9416 dan urine 9577) terkonfirmasi benar positif MA pada λ 215 nm dan 260 nm dan Rt 3,6 MS m/z ( 149, 134, 91,58), begitupun sebelumnya positif MDMA (urine 9768A1 dan urine 9768B) terkonfirmasi benar positif MDMA pada λ 215 nm, 240 nm dan 280 nm dan Rt 6,3 MS m/z ( 193, 178, 135, 89, 58 ). Munculnya warna spesifik senyawa MA warna orange kekuningan dan MDMA warna violet tua kekuningan oleh metode baru uji kolorimetri (spray Fast Blue B Salt) dapat diuji keselektivannya dengan TLC, HPTLC dan GCMS.